Adversity History Predicts Self-Reported Autonomic Reactivity and Mental Health in US Residents During the COVID-19 Pandemic - Kolacz, Jacek; Dale, Lourdes P.; Nix, Evan J.; Roath, Olivia K.; Lewis, Gregory F.; Porges, Stephen W. (Frontiers in Psychiatry, 2020)
Background: The spread of the COVID-19 virus presents an unprecedented event that rapidly introduced widespread life threat, economic destabilization, and social isolation. The human nervous system is tuned to detect safety and danger, integrating body and brain responses via the autonomic nervous system. Shifts in brain-body states toward danger-responses can compromise mental health. For those who have experienced prior potentially traumatic events, the autonomic threat response system may be sensitive to new dangers and these threat responses may mediate the association between prior adversity and current mental health. Method: The present study collected survey data from adult U.S. residents (n = 1666; 68% female; Age M = 46.24, SD = 15.14) recruited through websites, mailing lists, social media, and demographically-targeted sampling collected between March and May 2020. Participants reported on their adversity history, subjective experiences of autonomic reactivity, PTSD and depression symptoms, and intensity of worry related to the COVID-19 pandemic using a combination of standardized questionnaires and questions developed for the study. Formal mediation testing was conducted using path analysis and structural equation modeling. Results: Respondents with prior adversities reported higher levels of destabilized autonomic reactivity, PTSD and depression symptoms, and worry related to COVID-19. Autonomic reactivity mediated the relation between adversity and all mental health variables (standardized indirect effect range for unadjusted models: .212-.340; covariate-adjusted model: .183-.301). Discussion: The data highlight the important role of autonomic regulation as an intervening variable in mediating the impact of adversity on mental health. Because of the important role that autonomic function plays in the expression of mental health vulnerability, brain-body oriented therapies and exercises may be helpful during crisis.